Development Of Learning Video To Boost Grade IV Students Citizenship Learning Outcomes - Hikmah, Ulfah Nur; Ahmadi, Farid (Elementary School Teacher, 2019)
This study aims to determine the development, feasibility, and effectiveness of video media globalization of learning material in the subjects of Civics 4thgrade SDN 01 Purwoyoso Semarang. This research is a development (Research and Devlopment). The development model used is the Waterfall model. The population in this study are students of SDN 01 Purwoyoso totaled 27 students. Data collection techniques are test and non test. The development consists of five stages: analysis, design, implementation, testing, and maintenance. Results of the assessment of the material validator figures show the percentage of 82.14% to the category of "Eligible". As for the assessment of media validator figures show the percentage of 85% to the category of "Very Decent". Based on the results obtained by the Sig t test (two-tailed) of 0.000.Value Sig (2-tailed) of 0.000 0.05. It can be concluded that Ho is rejected and Ha accepted, which means there are significant differences between the learning outcomes of globalization Civics material before and after using the instructional video media. Thus instructional video media products is feasible and effective for use in the process of learning civics.